(untitled) (International Journal of Engineering and Computer Science, 2014)
Fuzzy Logic has been extremely vital role in the field of computer science, Artificial Intelligence, control theory and mathematic. Fuzzy logic is the way of organising belief or idea that cannot be defined precisely but which depends upon their contexts – human way of thinking, reasoning and perception. In this review paper we also see that the basics of fuzzy logic as well as fuzzy logic system (Fuzzy Inference System) use as decision making technique under a linguistic view of fuzzy sets.